2018
DOI: 10.1080/24750263.2018.1453554
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of native Mediterranean brown trout Salmo cettii Rafinesque, 1810 (Actinopterygii: Salmonidae) populations using an electric barrier as a mitigation tool

Abstract: This study assessed the effectiveness of a novel conservation strategy for the native brown trout populations in Sardinia (Italy). The conservation measures included: (i) installation of an electric fish barrier; (ii) removal of all the resident introgressed brown trout upstream from the barrier; (iii) restocking of the upstream region with native Sardinian trout genetically characterised; and (iv) estimation of native trout population size with prediction of future growth. Introgressed brown trout were remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The introduction of non-native cultured fish has been recognized as one of the most important threats to native trout populations in many countries [ 12 ], including Italy [ 5 ]. Recently, several conservation projects have been proposed to protect Mediterranean lineage trout populations [ 3 , 5 , 15 ]. In this regard, it must be emphasized that the importance of such projects goes beyond the single species conservation purpose considering also adverse ecological impacts of the stocked trout on ecosystem communities [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of non-native cultured fish has been recognized as one of the most important threats to native trout populations in many countries [ 12 ], including Italy [ 5 ]. Recently, several conservation projects have been proposed to protect Mediterranean lineage trout populations [ 3 , 5 , 15 ]. In this regard, it must be emphasized that the importance of such projects goes beyond the single species conservation purpose considering also adverse ecological impacts of the stocked trout on ecosystem communities [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, over the years, resource managers have adopted massive allochthonous restocking initiatives for balancing the effects of recreational overfishing. This had dramatically compromised the genetic variability of many Mediterranean trout native populations [ 3 , 12 ], thus several conservation projects have been recently proposed to restore native trout intraspecific biodiversity [ 3 , 5 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA molecular studies of different authors indicated that these insular populations harbour indeed very different genetic lineages. Corsican and Sardinian specimens are characterized by AD, MA and ME haplotypes (Sabatini et al 2011(Sabatini et al , 2018Lerceteau-Köhler et al 2013;Zaccara et al 2015;Berrebi et al 2019), while Sicilian ones are the only Italian trout having haplotypes belonging to the southern AT or African sub-clade (Schöffmann et al 2007;Snoj et al 2011;Fruciano et al 2014;Tougard et al 2018) (Figure 4). Thus, on the base of these consistent molecular data, the name Salmo cettii is useless for designating Tyrrhenian and insular (e.g., Kottelat & Freyhof 2007) or even all Italian Mediterranean trout (see Rondinini et al 2013;Lobón-Cerviá et al 2018).…”
Section: Geographic Rangementioning
confidence: 99%
“…Morphological data on Corsican trout is so far restricted to pyloric caeca counts (Olivari and Brun, 1988;Guyomard, 1989) and the description of variation in color pattern among populations (Lascaux et al, 2010). In the same way, the non-introgressed Sardinian populations were characterized by only the AD lineage and allele LDH-C1 100/ 100 (Sabatini et al, 2018). Some authors describe, for the Sardinian populations, different haplotypes with highly polymorphic characteristics accompanied by different phenotypes (Sabatini et al, 2011;Zaccara et al, 2015;Berrebi et al, 2019).…”
Section: Introductionmentioning
confidence: 96%